Szacowanie liczebności kopytnych w środowisku leśnym: przegląd metod - Chećko, Ewa (Leśne Prace Badawcze, 2011)
During the last few decades there has been a significant increase in abundance of forest ungulates in most Northern Hemisphere temperate zones. Large mammal herbivory is one of the most important factors shaping species composition, structure and function in temperate forest ecosystems. Furthermore, deer and wild boars are a cause of serious economic losses for forestry and agriculture, despite being a group of great interest to the public. The assessment of population size in forest habitats is a hot issue for both scientists and wildlife managers. Although there is an extensive literature on census methods and techniques, no agreement has been reached on a universally-applicable method for census of all species and conditions, fulfilling the criteria of being easy-to apply, cheap, precise and accurate. However, the implementation of some new methods (e.g. thermal imaging) seem to be very promising, but still need to be tested under closed canopy conditions in forest habitats. Ecological indicators that allow changes in the abundance of the animals to be monitored together with ecosystem properties may become an alternative resource for wildlife management, or at least can supplement wildlife census.